Maintenance pazopanib versus placebo in Non-Small Cell Lung Cancer patients non-progressive after first line chemotherapy: a double blind randomised phase III study of the lung cancer group, EORTC 08092 (EudraCT: 2010-018566-23, NCT01208064) - O'Brien, Mary; Schmid-Bindert, Gerald (European journal of cancer, 2015)
Background: Switch maintenance is an effective strategy in the treatment of advanced Non-Small Cell Lung Cancer (NSCLC). Pazopanib is an oral, multi-targeted tyrosine kinase inhibitor (TKI). EORTC 08092 evaluated pazopanib given as maintenance treatment following standard first line platinum-based chemotherapy in patients with advanced NSCLC. Methods: Patients with non-progressive disease after 4-6 cycles of chemotherapy were randomised to receive either pazopanib 800mg/day or matched placebo until progression or unacceptable toxicity. The primary end-point was overall survival and secondary end-points were progression-free survival (PFS) and safety. Results: A total of 600 patients were planned to be randomised. The trial was prematurely stopped following an early interim analysis, after 102 patients were randomised to pazopanib (n=50) or placebo (n=52). Median age was 64years in both arms. Median overall survival was 17.4months for pazopanib and 12.3months for placebo (adjusted hazard ratio (HR) 0.72 [95% confidence interval (CI) 0.40-1.28]; p=0.257). Median PFS was 4.3months versus 3.2months (HR 0.67, [95% CI 0.43-1.03], p=0.068). PFS rates at 4months were 56% and 45% respectively. The majority of treatment-related adverse events (AEs) were grade 1-2. Grade 3-4 AEs (pazopanib versus placebo) were hypertension (38% versus 8%), neutropenia (8% versus 0%), and elevated SGPT (6% versus 0%). Of the patients randomised to pazopanib, 22% withdrew due to a treatment-related AE. Conclusions: Switch maintenance with pazopanib following platinum-based chemotherapy in advanced NSCLC patients had limited side-effects. This study was stopped due to lack of efficacy by stringent criteria for PFS at a futility interim analysis.
Gesehen am 11.12.2018
Available online 11 June 2015